ANALISIS FINANSIAL PETERNAKAN SAPI PERAH RAKYAT DI KOTA TOMOHON (STUDI KASUS DIKELOMPOK RAMULU SANGKOR) - Labodu, Ray Paksi; Wantasen, Erwin; Massie, M T; Oroh, F. N.S (Universitas Sam Ratulangi, 2015)
ABSTRACT FINANCIAL ANALYSIS OF DAIRY CATTLE FARM IN TOMOHON CITY (CASE STUDY AT THE RAMULU SANGKOR FARMER GROUP). Study was conducted to analyze feasibility of the Ramulu Sangkor farmer group in Tomohon city. Study was implemented using survey method in the case study of the farm. Data were taken directly to thefarmer as primary data and taken from related institution as secondary data. Survey was done for March to April 2015. Data were analyzed using infestation criteria analysis including NPV, BC Ratio, IRR, ROI and profit analysis. Results showed that total investment were IDR 721.599.633/year and total receipt were IDR 951.217.667/year, of selling milk product and biogas. Therefore, it can be concluded that the Ramulu Sangkor farmer group was feasibly operated with NPV of IDR 448,929,526.-; BC Ratio of 2.880; IRR of 50.05, ROI of 41.82 and profit value of IDR 229.618.034.- for one months. Â Keywords: Dairy Cattle, Finance, Ramulu Sangkor Farmer Group